ANALISIS PENGARUH KEPEMIMPINAN DAN INSENTIF TERHADAP KINERJA PEGAWAI DENGAN MEDIASI MOTIVASI KERJA PADA DINAS KOMUNIKASI DAN INFORMATIKA PEMERINTAH KOTA BATU - Cahyawisesa Sri Rama Atmaja; Adya Hermawati; Rahayu Puji Suci (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to analyze the influence of leadership and incentives on employee performance with work motivation as a mediating variable at the Department of Communication and Informatics (Diskominfo) of Batu City. A quantitative approach was employed using a census method involving 55 employees. Data analysis was conducted using Partial Least Square-Structural Equation Modeling (PLS-SEM) via SmartPLS software. The results indicate that leadership and incentives have a positive and significant effect on work motivation. Directly, both leadership and incentives also significantly impact employee performance, with incentives being the most dominant factor. However, a unique finding emerged: work motivation does not significantly influence employee performance and fails to function as a mediating variable in all relational models. This phenomenon suggests that employees work pragmatically based on standard operating procedures (SOP) and rigid bureaucratic obligations. The research implications suggest strengthening transparent incentive systems and instructional leadership to maintain organizational productivity stability.